Cross-cultural adaptation of the writer-reader relationship in non-translated and translated English health information websites on HIV and TB diagnostic testing - Amy Dara Hochberg (Revista Alicantina de Estudios Ingleses)
The ideal multilingual health information website is relatable to all readers. Natives and immigrants should have a culturally adapted website in their language hosted by their place of residence that imparts the facts and incites a call to action to improve health, and ultimately reduces disease in the diverse community. The writer’s word choices and attitude as conveyed through the text influence the reader’s decision-making process. This paper will examine the differences between the non-translated and translated English versions of multilingual health information websites on HIV and TB diagnostic testing. These samples pertain to a large interdisciplinary study whose purpose is to determine whether the multilingual health communication websites are appropriately written regarding health literacy, and whether each cultural population, in terms of language adaptation, would receive the health information as intended. The study questions whether there exist differences between the translated and non-translated texts in English, Spanish and Catalan; this paper focuses on the two English sub-corpora. A comparable corpus of seventy-three multilingual health information websites underwent a quantitative and a qualitative analysis. The methodology is based on adaptations of Clerehan et al.’s (2005) Evaluative Linguistic Framework to assess the writer-reader relationship. The findings show statistically significant differences between the two English subcorpora as regards the writers’ and translators’ approach; the non-translated English sub-corpus contained more relational and engagement markers, whereas the translated English sub-corpus had more persuasion markers. These results should serve researchers and professionals in the translation and language sciences as well as the public health field for, respectively, future studies and techniques to improve the composition of multilingual health information texts in culturally diverse countries.